2016
DOI: 10.1002/2015wr018340
|View full text |Cite
|
Sign up to set email alerts
|

The psychology of recycled water: Factors predicting disgust and willingness to use

Abstract: Water recycling is increasingly recognized as a critical strategy to maintain sustainable water supplies. Yet public acceptance of water recycling often lags behind. It is unclear the degree to which individuals are aware of the role of disgust in their decisions about recycled water, how important anticipated disgust is to willingness to use when controlling for other factors, and what the most effective method of presenting information about water recycling would be to decrease disgust reactions and increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 75 publications
5
58
1
Order By: Relevance
“…These findings suggest that processing can mitigate some of the concern associated with recycled water found in previous studies. Consumers' lack of acceptance of fresh foods irrigated with recycled water may be related to aversion (Po et al, 2003;Wester et al, 2016;Kecinski et al, 2016Ellis et al, 2018a and/or its actual and perceived risks as discussed previously.…”
Section: ! 16mentioning
confidence: 99%
“…These findings suggest that processing can mitigate some of the concern associated with recycled water found in previous studies. Consumers' lack of acceptance of fresh foods irrigated with recycled water may be related to aversion (Po et al, 2003;Wester et al, 2016;Kecinski et al, 2016Ellis et al, 2018a and/or its actual and perceived risks as discussed previously.…”
Section: ! 16mentioning
confidence: 99%
“…Among them, Gibson & Burton's study has found that the use purpose of reclaimed water and exposure extent to the human are important factors that affect public willingness to accept reclaimed water reuse [5]. People's nauseous reaction to reclaimed water is the so-called "yuck factor", which has also been found as an important indicator of the willingness of people to accept reclaimed water [6][7][8]. There are also other scholars devoted to discovering the differences at the individual level and predicting the reusability of reclaimed water.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of the media and of communication regarding potable reused water has been discussed earlier, as well as the responses of populations to media messages [9][10][11][12][13][14]63,[114][115][116][117], and societal views on alternative sources of water [12,[117][118][119][120][121]. Here we discuss the views of the media, policymakers and water utility managers on the technology to produce potable reused water.…”
Section: Discussionmentioning
confidence: 99%